Generation Z's Experience Using Character.ai Application to Reduce Loneliness: A Case Study of Interpersonal Communication Based on Human-Machine Communication (HMC) - Mamarimbing, Gabriella Valentina; Tjahyana, Lady Joanne; Budiana, Daniel (Petra Christian University, 2026)
Generation Z is considered one of the loneliest generations. However, with the advancement of technology, it has become easier for Gen Z to communicate with others. In addition to social media, AI-based chatbots have become a popular option for overcoming loneliness through a form of interpersonal communication known as Human-Machine Communication (HMC). HMC-based interpersonal communication represents a significant breakthrough in the field of communication. With this, AI chatbots are now seen as more capable of engaging in communicative roles. These chatbots are increasingly accessible, with one example being the c.ai application. This study employs a qualitative approach, utilizing a case study method, to explore Generation Z's experiences in coping with loneliness through the use of Character.ai (c.ai). The app is found to help reduce feelings of loneliness, particularly during initial use. However, despite offering satisfying emotional responses, c.ai is still not considered a substitute for human interaction. If anything, c.ai was seen as a temporary solution or instant relief to reduce loneliness. Users may return to use the application, but they may also not, resulting in them searching for alternative ways to cope with their loneliness.